2008
DOI: 10.1149/1.2823739
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Behavior of Strained SiGe Layer on Silicon Substrate in Both Dry and Wet Ambient

Abstract: The oxidation behavior of a strained SiGe epitaxial layer on silicon substrate in both dry and wet ambient was investigated. We found that the oxide thickness at which oxidation saturation occurs increases with oxidation temperature and is larger for wet oxidation than dry oxidation at the same temperature, although Ge concentration at the oxidizing interface is much higher for wet oxidation. This observation shows that the oxidation saturation is not due to the thin, higher Ge-concentration layer at the oxidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…However, the decrease of degree of strain relaxation with oxidation time is against surface roughening and generation of dislocations. Considering the increase of critical thickness with lower Ge content [21] and volume expansion due to the transformation of SiGe to SiO 2 [13,22], we propose that the decrease of the degree of strain relaxation with oxidation time should be due to the lower Ge content and the stress relaxation of oxide layer viscously.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the decrease of degree of strain relaxation with oxidation time is against surface roughening and generation of dislocations. Considering the increase of critical thickness with lower Ge content [21] and volume expansion due to the transformation of SiGe to SiO 2 [13,22], we propose that the decrease of the degree of strain relaxation with oxidation time should be due to the lower Ge content and the stress relaxation of oxide layer viscously.…”
Section: Resultsmentioning
confidence: 97%
“…During this period, the Ge accumulation rate is much faster than diffusion rate leading to the formation of higher Ge content SiGe layers due to the high oxidation rate in wet ambient. However, when the oxidation time exceeds 30 min, the oxidation rate of the SiGe layer is markedly slowed and at last stops completely because of the self-limiting oxidation [12,13]. At this stage, the Ge atoms diffusion compared with the Ge condensation is dominant resulting in the decrease of Ge content of SiGe layers.…”
Section: Resultsmentioning
confidence: 99%
“…16. In addition, x-ray photon spectroscopy ͑XPS͒ measurements ensure that the formation of mixed oxide, SiO 2 and GeO 2 in the surface and the amount of GeO 2 is always very little at early stage.…”
Section: Resultsmentioning
confidence: 99%
“…During the oxidation of SiGe process, the Ge content and the degree of strain relaxation in the SiGe layer near the oxide interface increase with the oxidation time. 16 As a result, the increase in the lattice constant in in-plane direction of SiGe relieves the stress in SiO 2 to form loosening SiO 2 network, thereby enhancing the diffusion of O 2 . In addition, when SiO 2 was grown on the relaxed SiGe, the change in the volume of SiO 2 is smaller than that in the case of SiO 2 on Si substrate.…”
Section: A Region Imentioning
confidence: 99%
“…1- 6 Li et al 7 reported the oxidation behavior and strain relaxation of Si 1−x Ge x layer during dry and wet oxidations in which the oxidation saturation occurred due to mixture of GeO 2 and SiO 2 , and these oxide formation had a great influence on the strain relaxation due to a large volume expansion. Min et al 8 reported the formation of a Ge rich layer ͑GRL͒ and studied its behavior during the oxidation of strained-Si 1−x Ge x layers under different oxidation temperatures and times.…”
mentioning
confidence: 99%